Thermodynamics Performance Analysis of Solar-assisted Combined Cooling, Heating and Power System with Thermal Storage. (December 2017) - Lu, Yanchao; Wang, Jiangjiang
Abstract: The combined cooling, heating and power (CCHP) system is an energy efficient system that the premium characteristic is the energy cascade utilization. However, there is a mismatch problem between system supply and building demands. This paper proposes a solar-assisted CCHP system with thermal storage so as to effectively reduce the waste of energy. The components including solar heat collector, internal combustion engine and heat storage tank are modeled based their thermodynamic performances. An office building in Beijing is selected as a feasibility case and the impact of solar energy and thermal storage on the thermodynamics performance of the CCHP system is analyzed in detail. The results shows that when this system operates following thermal load, the system energy efficiency and COP decrease with the increase of solar energy, while exergy efficiency appears a slight fluctuation. Additionally, the variations of adjustable cooling compared to the system without thermal storage are discussed. It is concluded that thermal storage involved in the solar-assisted CCHP system contributes to expand the variations of adjustable cooling evidently.